Characterizing Fabrics in Firefighters' Protective Clothing: Hot Water Immersion with Compression. Issue 2 (March 2016) - Mandal, Sumit; Song, Guowen
This study characterized fabrics used in firefighters' protective clothing based on their response to thermal exposure using hot water immersion with compression. The thermal protective performance of compressed fabrics possessing different physical properties was evaluated based on thermal energy transmission under laboratory-simulated hot water immersion. Primarily, mass (hot water) transfer and conductive heat transfer occurred. Different fabric constructions and properties affected mass and heat transfer, affecting the thermal protective performance of the test fabrics. Fabrics including a moisture barrier possessed higher thermal protective performance than fabrics including no moisture barrier, even though the former fabrics had lower thermal resistance values. The position of the moisture barrier affected mass transfer through the fabric. Air-impermeable, heavy, and/or thicker fabric displayed higher thermal resistance and protective performance.